Clinical bleeding patterns and management of abnormal uterine bleeding in non-pregnant women: a cross-sectional study - Gupta, Anjali; Singh, Aradhana; Aditya, Vani; Tiwari, Harish Chandra; Chauhan, Mudit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Around 10 to 15 percent of women go through instances of unusual bleeding from their uterus at some point during their reproductive years. Additionally, up to one-third of women may come across irregular menstrual cycles. These irregularities often occur during two crucial phases in a woman’s life: firstly, at the beginning of menstruation, which is known as menarche, and secondly, during the transition leading up to menopause, referred to as perimenopause. Aim of study was to determine the clinical bleeding patterns in nonpregnant women and its management. Methods: During the study period spanning from November 2021 to December 2022, a cross-sectional study examined non-pregnant females aged 15 to 55 experiencing abnormal vaginal bleeding (AUB) who provided consent. However, certain exclusion criteria were established to ensure that the study’s findings remained pertinent to the target population. Females exhibiting vaginal bleeding attributed to pregnancy or pregnancy-related factors were excluded from the study, as were those with vaginal bleeding stemming from vaginitis, cervical benign, premalignant, or malignant conditions, or traumatic causes. Descriptive statistics were employed in the study. Results: Structural causes [PALM] accounts for 71 (61%) of cases whereas non-structural causes of chronic AUB account for 44 (39%) of cases. AUB-L, 45 (39.2%) was the most frequent finding in females with AUB. The second most common causes are AUB-O 23 (20%) followed by AUB-A 14 (12.2%), AUB-C 08(7%), AUB-M 07 (6.1%), AUB-E 06 (5.2%), AUB-P and AUB-I in 05 (4.3%) each and AUB-N 02 (1.7%). Conclusions: Focusing on Abnormal Uterine Bleeding (AUB), it was observed that AUB-L, attributed to leiomyomas, emerged as the most prevalent cause among affected females. Subsequently, AUB-O, arising from ovulatory dysfunction, and aub-a, linked to adenomyosis, ranked as the second and third most common causes, respectively. Among the clinical manifestations of AUB, prolonged bleeding was identified as the most frequent symptom, followed closely by heavy bleeding.